ANALISIS GERAKAN LITERASI SEKOLAH PADA SISWA KELAS IV SDN PODOREJO 01 KOTA SEMARANG: Penelitian Kualitatif Deskriptif - Fika Ananta Defi; Mei Fita Asri Untari; Khusnul Fajriyah (STKIP Subang, 2025)
This study examines the implementation of the School Literacy Movement (SLM) in fostering a reading culture among fourth-grade students at SDN Podorejo 01 Semarang City, focusing on teacher strategies, student achievements, and challenges faced. The research employed a descriptive qualitative method with data collected from the principal, teachers, and students through observation, interviews, and documentation. The findings reveal that SLM was implemented through activities such as reading for 15 minutes before lessons, providing reading corners, and utilizing the school library. Teacher strategies, including reading aloud, turn-taking reading, and book discussions, were effective in enhancing students’ reading interest and comprehension. However, several obstacles were identified, such as limited student enthusiasm, inadequate book collections, and minimal parental involvement in supporting reading at home. The study suggests enriching book collections, optimizing library management, strengthening parental engagement, and developing innovative literacy methods integrated into classroom learning to make the program more attractive, sustainable, and impactful.